Wiersze w średniowiecznych kronikach a strategia komunikacyjna nadawcy - Bering, Piotr (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The paper deals with inner organization of poems in medieval chronicles. The author examines various arts and registers of their. He also tries formulating a thesis of poem’s potentially dramatic organization.
Poems in the medieval chronicles and the sender’s communicative strategy
Medieval chronicles often contain some included poems according to principles of varietas. It is consider worthy, why they are located in precise defined particular places. Probably medieval poetics can deliver an answer. Unfortunately rhetorical rules and terms are often not fully exhaustive and do not clarify all poems occurrences. In some cases the dramatic text organization can explain using of particular poetical sequences. They serve as a commentary or an enrichment of used argumentation. A different situation is related to bigger dramatically organized text passages, which should be consider as a closed drama. A splendid example can be found in Chronica Polonorum written by Master Vincentius (Kadłubek). In this case a relationship between drama, theatre and rhetoric should be carefully examined.
Keywords: Rhetoric; drama; dramatization; medieval chronicle; medieval poetry; theory of drama